2019
DOI: 10.1029/2018jd029534
|View full text |Cite
|
Sign up to set email alerts
|

Forest‐Induced Exponential Growth of Precipitation Along Climatological Wind Streamlines Over the Amazon

Abstract: The Amazon forests and climatological precipitation patterns in South America are interrelated. A fundamental question is how these patterns depend on the presence of forests. Here we investigate this relationship by studying how precipitation varies with distance from the ocean along wind streamlines linking the Atlantic Ocean to northwestern and southern South America through the Amazon forests. Through a robust observation‐based analysis, we found that precipitation exponentially increases with distance fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 55 publications
0
36
0
3
Order By: Relevance
“…The seasonal precipitation over large parts of the Amazon region is mainly characterized by wet conditions in the austral summer, associated with the active phase of the South American Monsoon System (Vera et al, 2006;Zhou & Lau, 1998) and a dry season in austral winter, in the absence of the South American Monsoon System forcing. Moreover, several studies have shown that the Amazon basin itself constitutes a major moisture source for the region, driven by the hydrologic regime of the rainforest (Builes-Jaramillo & Poveda, 2018;Drumond et al, 2014;Molina et al, 2019;Salati et al, 1979). In fact, the forest induces dry season rainfall, necessary to sustain itself when oceanic moisture supply is limited (Staal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal precipitation over large parts of the Amazon region is mainly characterized by wet conditions in the austral summer, associated with the active phase of the South American Monsoon System (Vera et al, 2006;Zhou & Lau, 1998) and a dry season in austral winter, in the absence of the South American Monsoon System forcing. Moreover, several studies have shown that the Amazon basin itself constitutes a major moisture source for the region, driven by the hydrologic regime of the rainforest (Builes-Jaramillo & Poveda, 2018;Drumond et al, 2014;Molina et al, 2019;Salati et al, 1979). In fact, the forest induces dry season rainfall, necessary to sustain itself when oceanic moisture supply is limited (Staal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The southern Amazon is one of the most rapidly developing agricultural frontiers in the world, having experienced high rates of conversion of forest to croplands and pasturelands (Salazar et al, 2007;Instituto Nacional de Pesquisas Espaciais, 2014). Previous studies have demonstrated that these intense land use and land cover changes affect the regional precipitation (Lean et al, 1996;Costa and Foley, 2000;Davidson et al, 2012;Debortoli et al, 2015;Boers et al, 2017;Agudelo et al, 2019;Leite-Filho et al, 2019;Molina et al, 2019). These impacts are potentially important for the region, as some of its main economic activities, including agriculture, are highly dependent on climate (Sumila et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A PEN-induced dieback in the Amazon could tip the rainforest from a sink of carbon to a possible source (Davidson et al, 2012). This could in turn amplify the magnitude of extreme hydrological and weather events that occur during El Niño, such as droughts, in a positive-feedback-like manner (Zemp et al, 2017;Salazar et al, 2018), as well as disrupt mechanisms of river flow regulation (Salazar et al, 2018;Mercado-Bettin et al, 2019) and continental precipitation distribution (Molina et al, 2019). Near-synchronous effects of this sort between different tipping elements could give rise to a "tipping cascade" that could contribute to a planetary-scale state shift (Lenton and Williams, 2013 forest collapse in most of the Amazon, our results also agree with Betts et al (2008) that some areas in western Amazonia (adjacent to the Andes) are less vulnerable and could act as a refuge for biodiversity.…”
Section: Discussionmentioning
confidence: 99%